Model Of Learning Front Kick Skills In Pencak Silat - Suryani, Asih; Sulaiman, Iman; Widiastuti, Widiastuti; Subandi, Oman Unju; Taufik, Muhamad Syamsul (Department of Physical Education, Sport, Health and Recreation, 2023)
Abstract Pencak silat is expected to be able to provide provisions for children, especially early childhood for themselves now and in the future in martial arts, also besides that with this pencak silat it is hoped that the spirit This study aims to create a Model of Learning Front Kick Skills in Pencak Silat High School Athletes Aged 15-18 Years. The method used in this study is a research and development method based on Borg and Gall references. The subjects in this study were students of Senior High School in Karawanag Regency including students who had Pencak Silat martial arts skills for small group trials of 20 students, 60 athletes for large group trials, and in effectiveness trials of 60 athletes for. The instrument used in this study was to use the Pencak Silat Sports Front Kick Skill Test. This shows that there is an Influence Before and After the Learning Model is Given so that it can be said Based on the calculation of the t-Paired- ttest using SPSS, it is known that the value of t is -4.353 and the significance value of 2 directions (two-tailed) 0.000 < 0.05. This shows that there is a significant difference in scores before and after the model of learning front kick skills in high school athletes aged 15-18 years is effective.